Procalcitonin as a Marker of Bacterial Sepsis: Time for a Reappraisal? - Ahmed , Mohiuddin (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Sepsis is life-threatening organ dysfunction caused by a dysregulated host response to infection.1 It is frequently leading to death from septic shock and multi organ failure worldwide. Sepsis can be caused by any infection, either fungal, viral, parasitic, or bacterial, and not all of these pathogens can be cultured. In around half of patients with sepsis, no pathogen is identified.2 For every hour delayed treatment the risk of mortality from sepsis increases by 4-9%.3 Sepsis takes 11 million lives around the world each year, contributing to 20% of all deaths globally and taking more lives than cancer.4 There is more than 20 deaths every minute.5 Before the onset of organ dysfunction, infections should be identified and this requires a rapid diagnosis and a prompt initiation of treatment. J Bangladesh Coll Phys Surg 2023; 41:183-184